The effects of different packaging materials on physicochemical and sensorial properties of rempeyek / Nurul Azlin Tokiman... [et al.] - Tokiman, Nurul Azlin; Abdul Rahman, Nur Hazirah; Hajar, Nadya; Mohamad, Naemaa; Munawar, Nursabrina; Abd Rahim, Noor Hasvenda (Universiti Teknologi MARA, Negeri Sembilan, 2019)
This study was conducted to determine the effects of different packaging materials on the physicochemical and sensorial properties of traditional fried snack, Rempeyek. The samples were physically analysed for the texture (hardness) and color. Peroxide Value (PV) and Acid Value (AV) were the chemical analyses used to measure the rancidity level of Rempeyek during storage. On the other hand, Quantitative Descriptive Analysis (QDA) was conducted to describe the sensory characteristics of Rempeyek. All analyses were carried out for an interval of every month until 2 months of storage. The Rempeyek samples in this study were packed in five different types of packaging including Polyethylene Terephthalate (PETE or PET), PET with oxygen absorber, Low-Density Polyethylene (LDPE), LDPE with oxygen absorber and aluminium layer. In terms of hardness, Rempeyek that were packed in PET with oxygen absorber required the lowest force with 1198.93 ± 78.70 (g) while LDPE showed the highest force to break the sample with 2669.86 ± 905.72 (g) for 2 months of storage. The lightness (L*) and redness (a*) of Rempeyek decreased gradually while the yellowness (b*) displayed fluctuation readings along with the storage. Besides, the rancidity level of Rempeyek that was determined through PV significantly increased from 0 month (5.58 – 6.41 meq/g) to 2 months (14.42 – 39.75 meq/g) of storage. Similarly, the AV was significantly increased from 0 month (1.51 – 1.71 mg KOH/g) to 2 months (4.37 – 6.17mg KOH/g) of storage. In terms of QDA, the color of Rempeyek showed no significant changes but the score for aroma was significantly reduced from 0 month to 2 months of storage in LDPE and LDPE with oxygen absorber. Meanwhile, the scores for taste and hardness were reduced significantly from 0 month to 2 months of storage regardless of the types of packaging used.